Diaphorina citri Induces Huanglongbing-Infected Citrus Plant Volatiles to Repel and Reduce the Performance of Propylaea japonica - Lin, Yongwen; Lin, Sheng; Akutse, Komivi S.; Hussain, Mubasher; Wang, Liande (Frontiers in Plant Science, 2016)
Transmission of plant pathogens through insect vectors is a complex biological process involving interactions between the host plants, insects, and pathogens. Simultaneous impact of the insect damage and pathogenic bacteria in infected host plants induce volatiles that modify not only the behavior of its insect vector but also of their natural enemies such as parasitoid wasps. Therefore, it is essential to understand how insects such as the predator ladybird beetle responds to volatiles emitted from a host plant and how the disease transmission damages both insect vector and host plant. In this study, we investigated the response of Propylaea japonica to volatiles from citrus plants damaged by Diaphorina citri and Candidatus Liberibacter asiaticus through olfactometer bioassays. Synthetic chemical blends were also used to determine the active compounds in the plant volatile. The results showed that volatiles emitted by healthy plants attracted more P. japonica than other treatments, due to the presence of high quantities of D-limonene and beta-ocimene, and also the lack of methyl salicylate in uninfected plants. When using synthetic chemicals in the olfactory tests, we found that D-limonene attracted P. japonica while methyl salicylate repelled the predator. However, beta-ocimene attracted the insects at lower concentrations but repelled them at higher concentrations. These results indicate that P. japonica could not efficiently search for its host by using volatile cues emitted from psyllids- and Las bacteria-infected citrus plants.